Komunikasi Ritual Sedekah Gunung Merapi: (Studi Etnografi Komunikasi Desa Lencoh, Kecamatan Selo, Kabupaten Boyolali) - Fuaddah, Zamroatul (Universitas Islam Balitar, 2022)
The purpose of this study was to describe the pattern of community communication in the implementation of the Mount Merapi Alms ritual in Lencoh Village, Selo District, Boyolali Regency. The method used in this study is a qualitative method with an ethnographic approach to communication. The results of this study are the first communicative events in the Mount Merapi Alms ritual which is carried out to provide offerings to the supernatural creatures of Merapi residents in order to protect Lencoh Village which is under the slopes of Mount Merapi. Both communicative actions embody verbal and nonverbal behavior as expressions of gratitude, local cultural wisdom. The three communication activities are passed down from generation to generation by ancestors through traditional leaders to give a sense of togetherness to all creatures living on the slopes of Mount Merapi. Based on the communication pattern carried out by the community, it forms a cultural identity for the Selo community, Boyolali.